Effects of PCB 52 and PCB 77 on cell viability, [Ca2+]i levels and membrane fluidity in mouse thymocytes - Yilmaz, B; Sandal, S; Chen, CH; Carpenter, DO (Elsevier Ireland Ltd, 2006)
Exposure to polychlorinated biphenyls (PCBs) is known to suppress immune system function and this action is usually ascribed to dioxin-like PCBs that act via the Ah receptor. We have studied the effects of one ortho-substituted, non-dioxin-like PCB (PCB 52) and one coplanar, dioxin-like congener (PCB 77) on properties of thymocytes acutely isolated front mice, Viability of thymocytes was dose- and time-dependently reduced by PCB 52 with a threshold concentration of about 1 mu M, while there was no effect of PCB 77 on viability at concentrations less than 10 mu M. Cell death was detectible within 5 min of exposure. Both congeners caused a dose-dependent increase in [Ca2+](i), but the threshold concentration was 1 mu M for PCB 52 and 5 mu M for PCB 77, However, the cell death was not due to the elevation of [Ca2+](i), since it was not reduced by incubation in Ca-free Tyrode's Solution. PCB 52, but not PCB 77, caused an increase in membrane fluidity at a concentration of 5 mu M. These observations are consistent with previous results that suggest that ortho-substituted PCB congeners dissolve in cell membrane and cause greater disruption of function than do dioxin-like PCB congeners. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: flow cytometry; cell death; immune function; Ah receptor